Children's Hospital Transfers From Referring Emergency Departments: Which Patients Bypassed the Pediatric Emergency Department?. Issue 3 (March 2022) - Baca, Jacqueline E.; Foster, Carolyn C.; Simon, Norma-Jean E.; Lorenz, Doug; Gregg, Mary E.; Schinasi, Dana A.
Abstract : Objectives: Children are increasingly transferred from emergency departments (EDs) to children's hospitals for inpatient care. The existing literature on the use of direct admission (DA) specifically among pediatric patients transferred from referring EDs remains sparse. The objective of this study was to identify demographic, clinical, and contextual factors associated with the use of direct-to-inpatient versus ED-to-inpatient admission among patients transferred to children's hospitals from EDs. Methods: This was a retrospective chart review of nontrauma patients admitted to inpatient services at a single tertiary children's hospital after interfacility transfer from EDs between July 1, 2016, and June 30, 2017. Characteristics of the patient population and referring EDs were described; unadjusted associations between rates of DA and the demographic, clinical, and contextual variables of encounters were performed; and a logistic model quantified the relevant associations as odds ratios (ORs). Results: Of 2939 study encounters, 78% resulted in DA. Among White patients, private insurance was associated with decreased direct admission (OR, 0.5; 95% confidence interval [CI], 0.4–0.8). Younger patients and patients with respiratory diagnoses (OR, 3.9; 95% CI, 2.8–5.3) had increased likelihood of DA. Patients with gastrointestinal diagnoses had decreased likelihood of DA (OR, 0.6; 95% CI, 0.4–0.7). Conclusions: At a tertiary hospital with a high rate of DA among patients transferred from other EDs, we identified factors that were associated with the use of direct versus ED admission. Our results identify specific populations in which future work could inform admission processes for interfacility transfers. Abstract : Supplemental digital content is available in the text.